Sustainable human settlements within the global urban agenda : formulating and implementing SDG 11 - Simon, David (Newcastle upon Tyne : Agenda Publishing, 2024)
The UN's urban sustainability goal (#11) is fundamental to the global sustainable development agenda. David Simon explains the anatomy and dynamics of SDG 11, and critically assess how it is being used and understood in different local, regional and national contexts.
5.2 Suggested modifications and alternatives to SDG 11 -- 5.3 Challenges of subnational government implementation capacity -- 5.3.1 Multi-level governance -- 5.3.2 Cross-SDG integration -- 5.4 Appropriate funding and costs of implementation -- 5.5 Conclusions -- 6 Synthesis and conclusions -- 6.1 Introduction -- 6.2 Progress with implementation to date -- 6.2.1 Inadequate attention to SDG implementation in small towns -- 6.3 Smart cities, the SDGs and sustainability -- 6.4 Impact of the SDGs as a whole and Goal 11 in particular -- 6.5 Towards 2030: prospects for achieving SDG 11 -- Postscript -- References -- Index.
Includes bibliographical references and index.
Description based upon online resource; title from PDF title page (JSTOR, viewed December 4th, 2023).
eBooks on EBSCOhost
Keywords: Sustainable Development Goals (Project); Sustainable Development Goals (Project); Sustainable urban development -- Cross-cultural studies; Urbanisme durable -- Études transculturelles; Sustainable urban development; Cross-cultural studies